1982
DOI: 10.1037/0022-006x.50.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validation of the ability of the Luria-Nebraska Neuropsychological Battery to differentiate chronic schizophrenics with and without ventricular enlargement.

Abstract: The present study was an attempt to cross-validate discrimination rules derived from a previous study on the Luria-Nebraska Neuropsychological Battery for use in predicting ventricular enlargement and to replicate the correlations found between the Luria-Nebraska scales and ventricular brain ratio. Forty-three chronic schizophrenic patients between the ages of 20 and 39 were given a computed tomography (CT) scan and the Luria-Nebraska Battery. Ventricular brain ratio was calculated, and the Luria-Nebraska rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
(21 reference statements)
3
20
0
Order By: Relevance
“…The principal finding to emerge from these studies, and generally confirmed by several other investigators (Rieder et al, 1979;Andreasen et al, 1982;Golden et al, 1982), is that chronic schizophrenics show structural brain abnormalities in a variety of areas of the brain, most prominently enlarged ventricles, sulcal width, and cortical atrophy. Other abnormalities have included cerebellar atrophy , although smaller in magnitude than the rates of ventricular enlargement of approx 50% reported by Johnstone and Weinberger.…”
Section: Computed Tomography and Imaging Techniquessupporting
confidence: 61%
See 1 more Smart Citation
“…The principal finding to emerge from these studies, and generally confirmed by several other investigators (Rieder et al, 1979;Andreasen et al, 1982;Golden et al, 1982), is that chronic schizophrenics show structural brain abnormalities in a variety of areas of the brain, most prominently enlarged ventricles, sulcal width, and cortical atrophy. Other abnormalities have included cerebellar atrophy , although smaller in magnitude than the rates of ventricular enlargement of approx 50% reported by Johnstone and Weinberger.…”
Section: Computed Tomography and Imaging Techniquessupporting
confidence: 61%
“…There have been studies of the clinical relevance of CT scan abnormalities, demonstrating an association with negative symptoms (Andreasen et al, 1982), compromised cognitive-perceptual or neuropsychological functions (Reider et al, 1979;Golden et al, 1980Golden et al, , 1982Bilder et al, 1985;Pandurangi et al, 1986), impaired intelligence (Johnstone et al, 1976;Donnelly et al, 1980), premorbid asociality (Weinberger et al, 1980b), and diminished response to neuroleptics (Weinberger et al, 1980a). However, other studies are at variance with reports finding clinical correlates with ventricular enlargement (Krawiecka et al, 1977;Nasrallah et al, 1983).…”
Section: Computed Tomography and Imaging Techniquesmentioning
confidence: 99%
“…Even when schizophrenia patients and normal comparison subjects are equated for current IQ levels (Kremen et al, 2001) or when IQ is controlled for statistically (Seidman et al, 2002), patients still perform substantially more poorly on a variety of other neuropsychological measures. Despite the apparent ubiquity of neuropsychological impairment in schizophrenia, roughly a quarter of schizophrenia patients display apparently normal neuropsychological performance (Golden et al, 1982;Silverstein and Zerwic, 1985;Palmer et al, 1997;Kremen et al, 2000;Weickert et al, 2000;Allen et al, 2003). However, even this subgroup may have experienced decline from premorbid levels of cognitive ability (Kremen et al, 2000).…”
Section: Iq Versus Neuropsychological Functionmentioning
confidence: 99%
“…In fact, a few previous studies suggest that in some schizophrenia patients, NP abilities are unimpaired or normal [10,11]. To explore the prevalence and characteristics of schizophrenia patients with normal NP abilities Palmer et al conducted a study which included 171 clinically stable schizophrenia outpatients and 63 normal comparison (NC) participants.…”
Section: Can Schizophrenic Be Neuropsychologically Normal?mentioning
confidence: 99%